2007
DOI: 10.1002/bmb.56
|View full text |Cite
|
Sign up to set email alerts
|

A project‐based biochemistry laboratory promoting the understanding and uses of fluorescence spectroscopy in the study of biomolecular structures and interactions

Abstract: A laboratory project for a first semester biochemistry course is described, which integrates the traditional classroom study of the structure and function of biomolecules with the laboratory study of these molecules using fluorescence spectroscopy. Students are assigned a specific question addressing the stability/function of lipids, proteins, or nucleic acids, and asked to design an experiment to answer the question using fluorescence methodologies. Students study phase equilibria and determine the critical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Several well‐known biochemistry laboratory manuals have been published but I do not recall meeting any biochemists who teach their entire undergraduate biochemistry laboratory course from one of these texts. One or two experiments may be adopted, but we frequently develop our courses around projects that may connect to our research interests . The members of the team had all developed unique biochemistry teaching laboratory courses on their campuses and had all experimented to some extent with inquiry‐based learning.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several well‐known biochemistry laboratory manuals have been published but I do not recall meeting any biochemists who teach their entire undergraduate biochemistry laboratory course from one of these texts. One or two experiments may be adopted, but we frequently develop our courses around projects that may connect to our research interests . The members of the team had all developed unique biochemistry teaching laboratory courses on their campuses and had all experimented to some extent with inquiry‐based learning.…”
Section: Resultsmentioning
confidence: 99%
“…A recent search of the literature revealed 19 different articles about noncookbook teaching laboratories containing elements of research dating back to a 1975 article by Paul Melius entitled, “A creative, research approach to the undergraduate biochemistry laboratory” . Many of the article titles included the words “integrated” “project‐based” or “project‐oriented” . In addition, many of these courses were designed around a single enzyme or protein The incorporation of research in the teaching setting has been widely advocated .…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescence spectroscopy, which is used to measure the change in fluorescence intensity, can be used to study the interaction between compounds and DNA . However, CT‐DNA has very weak fluorescence in solution.…”
Section: Resultsmentioning
confidence: 99%
“…Hedley (2013) revealed that the use of geospatial technologies (GST) within a student/teacher/scientist partnership improved the geospatial skills and atmospheric science concept knowledge. Briese and Jakubowsk (2007) found that a laboratory project biochemistry course which integrates the traditional classroom study of the structure and function of biomolecules with the laboratory study improved understanding of the students on fluorescence spectroscopy. Differentiated teaching (Alexander, 2013), and experiential learning (Mohan, 2015) had statistically significant greater mean scores in academic performance and in critical thinking questions on the living environment, earth science and chemistry.…”
Section: The Student-centered Teaching Approach Problem-based Learnimentioning
confidence: 99%